2021
DOI: 10.1177/15347354211058678
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Hypnosis in Medical Care: A Mixed-Method Feasibility Study

Abstract: Background Preoperative hypnosis has shown promising effects in controlling side effects from breast cancer surgery, but the feasibility and effects are largely unknown outside the US. Methods A mixed-methods approach was applied involving a large-scale population survey and a small-scale pilot study. The survey assessed attitudes toward hypnosis in a representative sample from the general population (n = 1049), while the pilot study involved interviews with 5 women who received hypnosis prior to mastectomy/lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The scripted session includes a relaxation-based induction, suggestions for pleasant visual imagery, suggestions to experience relaxation and peace, and specific symptom-focused suggestions. The intervention has been thoroughly translated and piloted in a previous study that showed both feasibility and acceptability of hypnosis in this context [94]. Trained psychologists and last-year psychology students will provide the hypnosis in a dedicated room in the hospital.…”
Section: Interventionsmentioning
confidence: 99%
“…The scripted session includes a relaxation-based induction, suggestions for pleasant visual imagery, suggestions to experience relaxation and peace, and specific symptom-focused suggestions. The intervention has been thoroughly translated and piloted in a previous study that showed both feasibility and acceptability of hypnosis in this context [94]. Trained psychologists and last-year psychology students will provide the hypnosis in a dedicated room in the hospital.…”
Section: Interventionsmentioning
confidence: 99%
“…As recent research shows, the general public holds positive attitudes towards the use of hypnosis in medicine, 1 but there exist other third variables that should be incorporated and examined in any future research attempt.…”
mentioning
confidence: 99%